Enhanced photoluminescence response of Ca2+/Ba2+ substituted solid solutions of SrS: Ce phosphors - Vij, Ankush; Kumar, Shalendra; Won, S. O.; Chae, K. H.; Dubey, Abhinav; Kumar, Ravi (ELSEVIER SCIENCE BV, 2018)
The quest of improving luminescence efficiency in alkaline earth sulfide phosphors has been of great interest due to their applications in diverse areas. We synthesized SrS:Ce-0.05, Sr0.75Ba0.20S:Ce-0.05, Sr0.75Ca0.20S:Ce-0.05 and Sr0.75Ca0.10Ba0.10S:Ce-0.05 phosphors using solid state diffusion method. X-ray diffraction patterns of all the samples were found similar to the cubic SrS phase except minor shifts in angles. To ascertain the valence state of Ce, near edge X-ray absorption fine structure spectroscopy was employed using synchrotron radiations. We simulated Ce M-5,M-4-edges of Ce3+ ions using atomic multiplet calculations, which agrees well with the experimental data, clearly suggesting that Ce enters as Ce3+ in all the samples. The photoluminescence spectra of synthesized phosphors exhibit blue-green emission assigned to the 5d-4f transitions in Ce3+ levels, with minor shifts in wavelength. Interestingly, Ca2+/Ba2+ substitution in SrS: Ce phosphors increases the PL intensity considerably. In comparison to SrS: Ce-0.05, PL intensity of Sr0.75Ca0.10Ba0.10S:Ce-0.05 phosphors was enhanced by 2.7 times, which may be exploited in many optical applications. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: BI